2022
DOI: 10.1038/s41586-022-04898-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial RNA modifications shape metabolic plasticity in metastasis

Abstract: Aggressive and metastatic cancers show enhanced metabolic plasticity1, but the precise underlying mechanisms of this remain unclear. Here we show how two NOP2/Sun RNA methyltransferase 3 (NSUN3)-dependent RNA modifications—5-methylcytosine (m5C) and its derivative 5-formylcytosine (f5C) (refs.2–4)—drive the translation of mitochondrial mRNA to power metastasis. Translation of mitochondrially encoded subunits of the oxidative phosphorylation complex depends on the formation of m5C at position 34 in mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(116 citation statements)
references
References 56 publications
6
110
0
Order By: Relevance
“…Mitochondria possess specific translation machinery for the synthesis of proteins in ETC, and tRNA modification is indispensable during mitochondrial translation and the OXPHOS process, which require folate-dependent tRNA methylation [ 140 ]. A recent study indicates that mitochondrial tRNA methylation is necessary for tumor metastasis due to its critical role in mitochondria gene translation [ 141 ]. Moreover, tRNA methyltransferase 10C (TRMT10C), catalyzing the mitochondrial ND5 mRNA at N1-methyladenosine (m 1 A) site, promotes cancer cell metabolism by reducing the mitochondrial ribonuclease P protein 1 (MRPP1) in mitochondria and inducing protein instability and mt-tRNA processing [ 142 ].…”
Section: Mitochondria Function In Epigenetic Regulationmentioning
confidence: 99%
“…Mitochondria possess specific translation machinery for the synthesis of proteins in ETC, and tRNA modification is indispensable during mitochondrial translation and the OXPHOS process, which require folate-dependent tRNA methylation [ 140 ]. A recent study indicates that mitochondrial tRNA methylation is necessary for tumor metastasis due to its critical role in mitochondria gene translation [ 141 ]. Moreover, tRNA methyltransferase 10C (TRMT10C), catalyzing the mitochondrial ND5 mRNA at N1-methyladenosine (m 1 A) site, promotes cancer cell metabolism by reducing the mitochondrial ribonuclease P protein 1 (MRPP1) in mitochondria and inducing protein instability and mt-tRNA processing [ 142 ].…”
Section: Mitochondria Function In Epigenetic Regulationmentioning
confidence: 99%
“…Regarding CD36, a series of studies have demonstrated its metastasis-promoting functions [26][27][28][29]. However, CD36 has not been applied with 18 FDG-PET/CT for distinguishing false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…The biological impact and extent of RNA cytosine methylation are not entirely understood. However, the functional characterizations of NSUN proteins and the identification of their RNA substrates have helped uncover several essential roles played in the regulation of nuclear and mitochondrial gene expression (14,(18)(19)(20). Mutations and changes in expression levels of genes coding for several NSUN proteins have been linked with diverse human diseases ranging from neurological disorders (21) to cancer (22)(23)(24), highlighting the importance of further characterizing this family of RNA methyltransferases.…”
Section: Introductionmentioning
confidence: 99%